Utformning av sildammar för dränerade deponering av anrikningssand : tester i pilotskala vid LKABs anläggning i Malmberget - Åkerlund, Håkan (Luleå tekniska universitet, 2005)
In mining production, the refining process usually generates two different kinds of wastes; tailings and waste rock. Tailings and water from the refining process are pumped or conducted from the refining plant and usually disposed in a tailings dam, containing dammed water and tailings. Though this disposal method is widely used, it has some disadvantages. Most of them are related to the dammed water. To reduce the risks, tailings can be disposed under drained conditions with the use of seepage dams. The purpose of a seepage dam will be to stop the flow of tailing and at the same time drain the water away. An advantage with this method is the possibility to dispose the tailings on heights. This provides landscaping possibilities. If waste rock can be used when seepage dams are constructed the method will be economical beneficial. The aim of this work was to optimize the design of seepage dams. In order to do this a pilot plant was built, containing 4 cells with 4 different seepage dams. The seepage dams where constructed with waste rock. The total flow of tailings and water from the refining process was pumped into the test plant. During operation, the filtration and drainage capacity were measured. In a parallel study, the possibility to dispose tailings direct into waste rock also was tested.The filtration capacities were evaluated with two different methods and coefficients of efficiency were calculated. The coefficients varied between 34 - 100 % depending on the design of the seepage dams. An analysis of the sensitivity of the coefficient of efficiency shows that it will be best calculated based on a comparison between in pumped and disposed volume of tailings. The analysis also shows that the grain density is the parameter having the biggest influence on the calculated coefficient. With one exception, the drainage capacity was high in all cells.The disposal test shows, great variations of the pumped water and tailings. The flow velocity influences the deposition of tailings and the capacity of the seepage ...